2013
DOI: 10.1007/s11334-013-0201-3
|View full text |Cite
|
Sign up to set email alerts
|

Reusing models and properties in the analysis of similar interactive devices

Abstract: The paper is concerned with the comparative analysis of interactive devices. It compares two devices by checking systematically a set of template properties that are designed to explore important interface characteristics. The two devices are designed to support similar tasks in a clinical setting. The devices di↵er as a result of judgements based on a range of considerations including software. Variations between designs are often relatively subtle and do not always become evident through even relatively thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…Harrison et al carried out an investigation into the similarities of the models of two di↵erent safety-critical interactive systems in [28]. The purpose of this investigation is to see how much a model of a system can be re-used for a similar system.…”
Section: Existing Modelling Techniquesmentioning
confidence: 99%
“…Harrison et al carried out an investigation into the similarities of the models of two di↵erent safety-critical interactive systems in [28]. The purpose of this investigation is to see how much a model of a system can be re-used for a similar system.…”
Section: Existing Modelling Techniquesmentioning
confidence: 99%
“…For example, Rushby [24] used model checkers Murφ and SAL to verify mode confusion in a cockpit; Rukšėnas et al [21] used SAL to identify post-completion errors in infusion pumps; Campos and Harrison used IVY/NuSMV to analyze infusion pumps against properties such as consistency, visibility, and feedback [4,11]; and in our own work, we used SAL and Event-B/Rodin to analyze the data entry system of infusion pumps for their predictability [15,16] and other safety properties identified by FDA [22].…”
Section: Related Workmentioning
confidence: 99%
“…The present work builds on our previous research on the verification of medical device user interfaces [11,[14][15][16]22] and on user interface prototyping [19]. These previous efforts have demonstrated that formal methods can be used to identify human factors issues in reverse-engineered models of medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…A reference model is produced that satisfies a set of user interface properties and can be used as a standard against future versions of the design. The approach is based on model checking techniques using the IVY workbench [3], [4], a model-based tool for the analysis of interactive systems, which has shown its potential to be used in other critical areas [5], [6]. Analysis uses models that are constructed of the user interfaces under analysis.…”
Section: Introductionmentioning
confidence: 99%